Best practice recommendations: ENT consultations during the COVID-19 pandemic - Lescanne, E. (Eur Ann Otorhinolaryngol Head Neck Dis, 2020)
These best practice recommendations for ENT consultations during the COVID-19 pandemic have been drawn up because ENT examinations and treatments are at risk of contamination by the SARS-Cov-2 virus in certain instances. Thus, ENT specialists are among the professionals who are most exposed to this infection. During the pandemic, insofar as an asymptomatic patient may be infected and contagious, the same precautions must be employed whether the patient is ill with, suspected of having, or without any clinical evidence of COVID-19 infection. According to the scientific data available, the examinations and procedures potentially exposing to projections/aerosolizations of organic material of human origin are considered to be at risk of staff contamination. For ENT examinations and procedures without exposure to such projections/aerosolizations, the professional is advised to a long sleeve clean outfit, a surgical mask and gloves in case of contact with the patient's mucosa. ENT examinations and procedures with exposure to these projections/aerosolizations require the so-called “airborne”, “contact”, and “droplets” additional precautions: FFP2/N95 respiratory protection device, eye protection, disposable headwear and long sleeve overgown.